2010
DOI: 10.1152/ajplung.00026.2010
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive intratracheal bleomycin models several features of idiopathic pulmonary fibrosis

Abstract: Single-dose intratracheal bleomycin has been instrumental for understanding fibrotic lung remodeling, but fails to recapitulate several features of idiopathic pulmonary fibrosis (IPF). Since IPF is thought to result from recurrent alveolar injury, we aimed to develop a repetitive bleomycin model that results in lung fibrosis with key characteristics of human disease, including alveolar epithelial cell (AEC) hyperplasia. Wild-type and cell fate reporter mice expressing β-galactosidase in cells of lung epithelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
248
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 245 publications
(268 citation statements)
references
References 43 publications
12
248
1
Order By: Relevance
“…We have previously shown that the number of TUNEL+ epithelial cells peaks in the lungs at 1 wk after i.t. bleomycin injection (17). At this time point, lung sections from L188Q SFTPC mice showed greater numbers of TUNEL+ AECs than lungs from WT controls did (Fig.…”
Section: Expression Of L188q Sftpc Increases Aec Apoptosis After Bleomentioning
confidence: 74%
See 3 more Smart Citations
“…We have previously shown that the number of TUNEL+ epithelial cells peaks in the lungs at 1 wk after i.t. bleomycin injection (17). At this time point, lung sections from L188Q SFTPC mice showed greater numbers of TUNEL+ AECs than lungs from WT controls did (Fig.…”
Section: Expression Of L188q Sftpc Increases Aec Apoptosis After Bleomentioning
confidence: 74%
“…3D). In previous studies, we have used S100A4 as a fibroblast marker in the lungs (14)(15)(16)(17). Therefore, we evaluated lung sections by IHC for S100A4 expression and noted greater numbers of S100A4-positive fibroblasts in L188Q SFTPC mice compared with WT controls after bleomycin treatment ( Additionally, we wanted to determine whether lung mechanics were different at 3 wk after bleomycin treatment in L188Q SFTPC mice.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three sections per mouse were measured. On lung sections, fibrosis development was scored as previously described (22). Average scores were calculated by scoring 3 different fields of view per slide, and 2 slides per lung were scored in a blinded manner.…”
mentioning
confidence: 99%